STUDI DYNAMIC PATTERN DENGAN KOMBINASI SUMUR VERTIKAL DAN SUMUR INFILL LATERAL PADA POLA LIMA TITIK RESERVOAR TIPIS - Ichsan, Muhammad
This research uses software to simulate a reservoir to know the recovery factor of production methods used. The production methods used in this research are water injection, surfactant injection, and dynamic pattern concept with lateral infill wells added. First, water is injected into the reservoir by the vertical well in five spot pattern until the certain water cut value. Then, it is continued by injecting the surfactant in the certain concentration until the certain water cut value. Then, it is continued by applying the dynamic pattern concept by changing the production and injection pattern, in the same time, the lateral infill wells are added. The dynamic pattern concept with lateral infill wells added is applied to repair the swept efficiency to increase the value of recovery factor.